Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1007/bf01959214
|View full text |Cite
|
Sign up to set email alerts
|

Ifosfamide nephrotoxicity in paediatric cancer patients

Abstract: Ifosfamide is an alkylating agent which has been incorporated into frontline therapy for a number of malignant paediatric tumours. Recent data appears to suggest that tubular dysfunction may result from incorporation of this drug into chemotherapy schedules and that toxicity may be dose related. A detailed investigation of renal function was performed in a group of patients, ranging in age from 8 months to 15.9 years (median 8.6 years) with rhabdomyosarcoma (n = 11) and Ewing's sarcoma (n = 9) who were current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…A diagnosis of Fanconi's syndrome was documented as far as 3 years following cessation of treatment [63]. This has been supported by previous studies which found that most patients received a diagnosis of Fanconi's syndrome in 2 years after treatment [49,64].…”
Section: Inter-individual Variabilitysupporting
confidence: 53%
See 2 more Smart Citations
“…A diagnosis of Fanconi's syndrome was documented as far as 3 years following cessation of treatment [63]. This has been supported by previous studies which found that most patients received a diagnosis of Fanconi's syndrome in 2 years after treatment [49,64].…”
Section: Inter-individual Variabilitysupporting
confidence: 53%
“…More severe proximal tubule toxicity can result in Fanconi's syndrome with clinically-relevant hypophosphatemic rickets, proximal renal tubule acidosis and hypokalemia [19,[49][50][51]. Chronic glomerular dysfunction, evident by reduced glomerular filtration rate (GRF) and elevated serum creatinine, may coexist [19,42,49]. Although relatively uncommon [43], severe distal toxicity, when present, can lead to diabetes insipidus and distal renal tubular acidosis [51,52].…”
Section: Clinical Presentation Of Ifo-induced Nephrotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…While subclinical glycosuria was detected in 88% of patients in a large study [14], clinically significant abnormalities including Fanconi syndrome occur in between 1.3 and 27% of treated patients [11, 17, 23, 24]. Risk is increased by prior or concurrent platinum chemotherapy [11, 13, 15, 25, 26], increasing cumulative ifosfamide dose [1214, 17, 25, 27], and reduced functioning nephron mass [13, 23, 25, 28], but not scheduling of ifosfamide dose [29, 30]. Whether aminoglycoside use increases risk is unclear [14, 31] although aminoglycosides per se may cause Fanconi syndrome [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although early studies failed to reveal any evidence of nephrotoxicity in children receiving ifosfamide (de Kraker and Voute, 1984;Gasparini, 1986;Biron et al, 1987;Kellie et al, 1988;Demeocq et al, 1989), subsequent reports described a characteristic pattern of proximal renal tubular damage, often accompanied by glomerular and sometimes by distal tubular impairment (Smeitink et al, 1988;Burk et al, 1990;Skinner et al, 1990;Pratt et al, 1991;Suarez et al, 1991;Caron et al, 1992;Shore et al, 1992;De Schepper et al, 1993;Arndt et al, 1994;Ashraf et al, 1994). Such toxicity persisted long after discontinuation of ifosfamide treatment in many patients, often presenting with clinical manifestations due to the Fanconi syndrome (Skinner et al, 1993).…”
Section: Discussionmentioning
confidence: 99%